Experimental study on a breaking-enforcing floating breakwater - van der Zanden, Joep; van der Hout, Arne; Otto, William; Spaargaren, Floor; Walles, Brenda; de Wilde, Jaap (Journal of Coastal and Hydraulic Structures, 2022)
Floating breakwaters are moored structures that attenuate wave energy through a combination of reflection and dissipation. Studies into floating breakwaters have been generally restricted to optimising the attenuation performance. This study presents a novel floating breakwater type that was developed to have good attenuation performance while keeping wave drift loads as small as possible. The floating breakwater was designed as a submerged parabolic beach that enforces wave energy dissipation through breaking. The design was tested in a 3D shallow-water wave basin in captive and moored setups for regular and irregular wave conditions. Results are presented in terms of attenuation performance, motions, and (mooring) loads. The results show that the breaking of waves improves the attenuation performance of the floater in captive setup. However, in moored setup, the attenuation performance was dominated by diffraction and radiation of the wave field, with breaking being of secondary importance. This shows that breaking-enforcing floating breakwaters have potential, but require a high vertical hydrostatic and/or mooring stiffness in order to enforce intense breaking. Mean wave drift loads on the object showed significant difference between breaking and non-breaking waves in both setups, with breaking waves leading to lower normalized loads. This is attributed to breaking-induced set-up and set-down of the water level. As a result, the new breakwater design has a more favourable balance between wave attenuation and drift loads than common (i.e., box-, pontoon-, or mat-type) floating breakwater designs. Tests with varying surface roughness showed that floating breakwaters may benefit from dual-use functions that naturally increase the roughness (e.g., shellfish, vegetation), which have a marginal effect on the attenuation performance, but increase the added mass and hydrodynamic damping and as such, reduce mooring line loads.